2010
DOI: 10.1186/1758-3284-2-29
|View full text |Cite
|
Sign up to set email alerts
|

Electronic versus paper diaries: a pilot study of concordance and adherence in head and neck cancer patients receiving radiation therapy

Abstract: BackgroundInteractive Voice Response Systems (IVRS) and other electronic data collection methods have begun to replace conventional paper diaries as a way to capture daily patient reports. However, these methods have not been compared in head and neck (H&N) cancer patients receiving radiation therapy.Methods15 subjects with H&N cancer were asked to complete daily IVRS calls and daily paper diaries during radiation therapy. We compared response consistency and comparative adherence across the two methods.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
4
1
2
Order By: Relevance
“…In a previous study of head and neck cancer patients undergoing radiation therapy [4], we demonstrated high concordance between paper diaries and IVR. However, paper diaries yielded greater adherence, though adherence indicators for paper diaries are less verifiable.…”
Section: Introductionsupporting
confidence: 60%
“…In a previous study of head and neck cancer patients undergoing radiation therapy [4], we demonstrated high concordance between paper diaries and IVR. However, paper diaries yielded greater adherence, though adherence indicators for paper diaries are less verifiable.…”
Section: Introductionsupporting
confidence: 60%
“…A menudo se utilizan materiales audiovisuales o enviados por correo e instrucciones por teléfono. Hoy en día los celulares son un método popular que se está usando para ayudar a los pacientes a recordar la toma de sus medicamentos, al igual que los mensajes de texto; también algunos pacientes reportan el uso de relojes de alarma o temporizadores de cocina (67) ; sin embargo hay que tener en cuenta que estos métodos no son tan efectivos con personas de mayor edad ya que no dominan el uso de esta tecnología o no están dispuestos a utilizarla (70) . (2) Intervenciones centradas en el comportamiento, las cuales tienen como objetivo orientar, formar o reforzar patrones específicos del comportamiento.…”
Section: Métodos Y Técnicas De Evaluación E Intervención Para Los Problemas De Adherencia Al Tratamiento Oncológicounclassified
“…In addition to these problems, which according to the literature are common-place, additional issues relating to ‘back-filling’ of diary entries can also adversely affect the quality and reliability of the data collected [22]. A study by Stone et al [22] found much better diary completion compliance when using electronic diaries as opposed to paper diaries (94% vs. 11% respectively); however, other studies have not replicated this finding [23]. Whilst financial limitations would rule out the use of electronic diaries for our subsequent study, the paper data collection diaries will be reviewed with a view to simplifying them and making their completion less onerous.…”
Section: Discussionmentioning
confidence: 99%